2011
DOI: 10.3945/ajcn.111.013219
|View full text |Cite
|
Sign up to set email alerts
|

A higher ratio of beans to white rice is associated with lower cardiometabolic risk factors in Costa Rican adults

Abstract: Increasing the ratio of beans to white rice, or limiting the intake of white rice by substituting beans, may lower cardiometabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 32 publications
5
41
1
7
Order By: Relevance
“…The positive association between high triglycerides and low HDL with white rice consumption in the North region confirms some previous studies[1215, 38], whereas others found no association[5, 10]. Possible explanations for our findings could be enhanced hepatic synthesis of VLDL[39], or decreased clearance of apoB-containing particles related to reduced lipoprotein lipase activity induced by high carbohydrate intake[40, 41].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The positive association between high triglycerides and low HDL with white rice consumption in the North region confirms some previous studies[1215, 38], whereas others found no association[5, 10]. Possible explanations for our findings could be enhanced hepatic synthesis of VLDL[39], or decreased clearance of apoB-containing particles related to reduced lipoprotein lipase activity induced by high carbohydrate intake[40, 41].…”
Section: Discussionsupporting
confidence: 87%
“…White rice is a major staple food in Asia, but with regional variation [ranging from high (Southern China) to low (Central China) consumption]. The literature on rice consumption and T2DM is mixed[411], ranging from positive[8, 10, 11], null[4, 5, 9] to negative[7], as is the association with markers of dyslipidemia [positive or no association with high triglycerides and/or low high-density lipoprotein (HDL)[5, 10, 1215]]. These inconsistent findings may relate to the nature of samples studied, quality of diet data, or different biological effects rather than heterogeneity in results across studies.…”
Section: Introductionmentioning
confidence: 99%
“…These values for prevalence of MetS in Latin America are similar to the ranges obtained for adult people in Europe and USA [18]–[20]. Therefore, Mexico shows a considerably higher prevalence of MetS than the nearest countries, such as El Salvador (28.8%) [21], Guatemala (22.7% in men, and 41.1% in women) [22] and Costa Rica (29.2%) [23], and present findings from the State of Nuevo León also show results above this range. The cause of this trend may be related to changes in lifestyle, characterized by a higher energy intake and low physical activity, as well as by massive migrations from rural to urban areas [24].…”
Section: Discussionsupporting
confidence: 78%
“…A large Danish prospective cohort study of the impact of replacing saturated fats with high-GI carbohydrates found that when high-GI carbohydrates replace saturated fat, myocardial infarction (MI) risk increases 33% (106). A meta-analysis of 10 prospective cohort studies (n=296,849) (107) found increased GL associated with a 27% increased coronary heart disease (CHD) and MI risk (108). In controlled-feeding studies, replacing saturated fat with carbohydrates lowers low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol and increases triglycerides (109).…”
Section: Macronutrients Foods and Cvd Risk Factorsmentioning
confidence: 99%